Correlation of hemogram parameters with acute phase reactants in subacute thyroiditis - Şen Uzeli, Ülkem; Doğan, Murat (Journal of health sciences and medicine : (Turkey), 2024)
Aims: Subacute thyroiditis is a painful, inflammatory thyroid gland disease. It manifests clinically with thyrotoxicosis and an increase in acute-phase reactants. In our study, we aimed to investigate the correlation between hemogram parameters (neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), pan-immune inflammatory value (PIV), and systemic immune-inflammatory index (SII)) and elevated acute phase reactants during the diagnosis of this disease where inflammation is prominent. Methods: Our study is a retrospective analysis involving 48 subacute thyroiditis (SAT) patients and 48 healthy control subjects. Thyroid function tests (TSH, FT4, and FT3), complete blood count values including white blood cell, neutrophil, monocyte, lymphocyte, and platelet counts, and C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were recorded for the patients. The relationship between hemogram parameters, acute phase reactants, and thyroid function tests at the time of diagnosis and six months after starting treatment was analyzed. Results: The female count in the patient group was 34 (70.8%), and in the healthy group, it was 29 (60.4%) in our study. There was no statistically significant difference in gender distribution between the groups. NLR, PLR, PII, and SII were significantly higher in SAT patients at the time of diagnosis. We found a positive correlation between CRP levels and SII and PIV and between ESR levels and PLR and PIV at the time of diagnosis. Conclusion: As a practical biomarker, PIV was significantly higher in patients with SAT compared with the control group. Our study is the first to show that PIV may be a new diagnostic tool for SAT.